Total factor productivity estimation: A practical review - Ilke Van Beveren (Katholieke Universiteit Leuven, LICOS Centre for Institutions and Economic Performance, 2007)
This paper aims to provide empirical researchers with an overview of the methodological issues that arise when estimating total factor productivity at the establishment level, as well as of the existing techniques designed to overcome them. Apart from the well-known simultaneity and selection bias; attention is given to methodological issues that have emerged more recently and that are related to the use of deflated values of inputs and outputs (as opposed to quantities) in estimating productivity at the firm level, as well as to the endogeneity of product choice. Using data on single-product firms active in the Belgian food and beverages sector, I illustrate the biases introduced in traditional TFP estimates and discuss the perfirmance of a number of alternative estimators that have been proposed in the literature.
Keywords: C13; C14; D24; D40; 330; Total factor productivity; Imperfect competition; Endogenous product choice; Semiparametric estimator; Demand; Produktivität; Unvollkommener Wettbewerb; Nahrungsmittelgewerbe; Schätztheorie; Belgien